Fine-resolution Upper Weichselian and Holocene palynological record from Navarrés (Valencia, Spain) and a discussion about factors of Mediterranean forest succession - Carrión, J. S.; Geel, B. Van (Review of Palaeobotany and Palynology, 1999)
A detailed study is presented of the Upper Pleistocene and Holocene pollen sequence of the Navarre´s peat deposit (Valencia, eastern Spain) including non-pollen palynomorphs, Characeae gyrogonites, seeds and charcoal abundance. The study covers the period from ca. 30,900 to 3160 yr B.P. The last glacial vegetation is characterised by Pinus–Artemisia– Ephedra assemblages. This dominance is interrupted between ca. 30,260 and 27,890 yr B.P. by the development of Quercus, Pinus pinaster, deciduous trees and Mediterranean shrubs, suggesting the proximity of glacial refugia and an expansion of their vegetation under inﬂuence of a milder climate. A Younger Dryas signal is noticed by increases of Artemisia and Ephedra around 10,380 yr B.P. There is no immediate response of Quercus to the Late Glacial and Holocene climatic ameliorations and Pinus continues to dominate the landscape until removed at ca. 5930 yr B.P., presumably by severe ﬁre events whose causes are discussed in the light of palynological, anthracological and paleoclimatical data
Keywords: Holocene; navarrés; paleoecology; pollen; quaternary; Spain; vegetation history; younger dryas

Fine-resolution Upper Weichselian and Holocene palynological record from Navarrés (Valencia, Spain) and a discussion about factors of Mediterranean forest succession - Carrión, J S; Geel, B Van (Review of Palaeobotany and Palynology, 1999)
A detailed study is presented of the Upper Pleistocene and Holocene pollen sequence of the Navarre´s peat deposit (Valencia, eastern Spain) including non-pollen palynomorphs, Characeae gyrogonites, seeds and charcoal abundance. The study covers the period from ca. 30,900 to 3160 yr B.P. The last glacial vegetation is characterised by Pinus–Artemisia– Ephedra assemblages. This dominance is interrupted between ca. 30,260 and 27,890 yr B.P. by the development of Quercus, Pinus pinaster, deciduous trees and Mediterranean shrubs, suggesting the proximity of glacial refugia and an expansion of their vegetation under inﬂuence of a milder climate. A Younger Dryas signal is noticed by increases of Artemisia and Ephedra around 10,380 yr B.P. There is no immediate response of Quercus to the Late Glacial and Holocene climatic ameliorations and Pinus continues to dominate the landscape until removed at ca. 5930 yr B.P., presumably by severe ﬁre events whose causes are discussed in the light of palynological, anthracological and paleoclimatical data
Keywords: Holocene; navarrés; paleoecology; pollen; quaternary; Spain; vegetation history; younger dryas